Effect of the nickel precursor on deactivation of Ni/SiO2 catalysts during thermal catalytic decomposition of methane at 823 K - Aldana, José; Calafat, ílvaro; Sánchez, Nora (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The effect of the nickel precursor [Ni(NO3)2 or Ni(O2C2H3)2] on deactivation of Ni/SiO2 catalysts for thermo catalytic decomposition (TCD) of methane at 823 K has been investigated. TCD of methane was studied by the thermogravimetric method, monitoring the mass change of the catalyst due to carbon deposition. The samples were characterized by X-ray diffraction and temperature programmed reduction. The catalysts prepared from Ni(O2C2H3)2 showed a better performance in TCD of methane compared with those prepared from Ni(NO3)2, due to the lower catalyst deactivation constant showed. Ni metal particles tended to disperse during the reaction on the catalysts prepared from Ni(NO3)2, while those tended to sinter when catalysts were prepared using Ni(O2C2H3)2. The capability of the catalytic system to maintain a suitable metal particle size for methane decomposition was related to the metal-support interaction, which was stronger on the catalysts prepared from Ni(O2C2H3)2. It is suggested that the occurrence of fragmentary dispersion or atomic erosion were the main reason for the rapid deactivation of catalysts prepared from Ni(NO3)2.